Acupuncture combined with repetitive transcranial magnetic stimulation for the treatment of post-stroke depression: a systematic evaluation and meta-analysis based on a randomised controlled trial - Xiao, Keyuan; Li, Xiang; Hu, Wenqing; Li, Xinghua (Frontiers in Neurology, 2024)
Objective This study aimed to systematically assess the efficacy of combining acupuncture with repetitive transcranial magnetic stimulation (rTMS) in treating post-stroke depression (PSD). Methods We conducted a comprehensive search of eight major domestic and international databases, including the China Knowledge Network, from inception until December 2023. Included were randomized controlled trials that investigated acupuncture combined with rTMS for PSD. The screening process adhered to predetermined inclusion and exclusion criteria, and study quality was assessed using Cochrane Handbook 5.1 guidelines. Meta-analysis was conducted using RevMan 5.4 software. Results Twelve studies involving 800 patients were included in the analysis. The meta-analysis showed that acupuncture combined with rTMS significantly improved the clinical effectiveness rate (RR = 1.19, 95% CI: 1.12 to 1.27, p < 0.00001) and reduced scores on several scales: Hamilton Depression Scale (HAMD) (MD = −3.35, 95% CI: −3.79 to −2.90, p < 0.00001), Self-Depression Scale (SDS) (MD = −9.57, 95% CI: −12.26 to −6.89, p < 0.00001), Chinese Medicine Symptom Score (MD = −3.34, 95% CI: −3.76 to −2.91, p < 0.00001), Pittsburgh Sleep Quality Scale (MD = −3.91, 95% CI: −4.58 to −3.25, p < 0.00001), and National Institutes of Health Stroke Scale (NIHSS) (MD = −2.77, 95% CI: −3.21 to −2.32, p < 0.00001). Furthermore, acupuncture combined with rTMS treatment improved cognitive functioning (MMSE, MoCA scores) (p < 0.00001) and ability to perform activities of daily living scores (MD = 10.40, 95% CI: 9.53 to 11.28, p < 0.00001). Additionally, it was found to reduce interleukin 6, tumor necrosis factor alpha, interleukin 1β, and increase 5-hydroxytryptamine and brain-derived neurotrophic factor levels (p < 0.001). Conclusion Acupuncture combined with rTMS therapy is recommended for treating PSD, as it effectively improves clinical outcomes, alleviates depressive symptoms, enhances cognitive function, and daily living capabilities, and modulates inflammatory responses and neurotransmitter levels. However, it is important to note that the limitations of the sample size and quality of the included studies warrant the need for more high-quality research to validate these conclusions. Systematic review registration INPLASY, Identifier INPLASY202430085.